2023
DOI: 10.1101/2023.03.08.23286979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of IgG and IgM to SARS-CoV-2 and other human coronaviruses in The Democratic Republic of Congo, Sierra Leone and Uganda: A Longitudinal Study

Abstract: Objectives We assessed the prevalence of immunoglobulin G (IgG) and immunoglobulin M (IgM) against four endemic human coronaviruses (HCoVs) and two SARS-CoV-2 antigens, among vaccinated and unvaccinated staff at health care centres in Uganda, Sierra Leone, and the Democratic Republic of Congo (DRC). Methods Government health facility staff who had patient contact in Goma (DRC), Kambia District (Sierra Leone), and Masaka District (Uganda) were enrolled. Questionnaires and blood samples were collected at three t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Within the 2021 blood donor cohort, seroprevalence reached 61%. This finding is slightly lower than others in the country which have reported up to 70% 13,14,48 and similar to surveys in Somalia, 18 Uganda, 19 Nigeria, 22 Burkina Faso 49 or South Africa 50,51 where antibody detection between 56% and 67% by 2021 has been reported. Although much lower seroprevalence has been estimated in studies in the Republic of the Congo (31.8%) 11 and Gabon (13%), 52 both relied on lateral‐flow rapid immunochromatography tests, which could justify the difference.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Within the 2021 blood donor cohort, seroprevalence reached 61%. This finding is slightly lower than others in the country which have reported up to 70% 13,14,48 and similar to surveys in Somalia, 18 Uganda, 19 Nigeria, 22 Burkina Faso 49 or South Africa 50,51 where antibody detection between 56% and 67% by 2021 has been reported. Although much lower seroprevalence has been estimated in studies in the Republic of the Congo (31.8%) 11 and Gabon (13%), 52 both relied on lateral‐flow rapid immunochromatography tests, which could justify the difference.…”
Section: Discussionsupporting
confidence: 76%
“…Cross‐reactivity of pre‐pandemic samples from African patients has raised concerns regarding the analytic performance of the commercially available testing platforms 14,28,63 . Our study shows over 90% global sensitivity in all assays except IgM+A detection.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…One national survey in March 2021 reported an overall immunoglobulin G (IgG) antibody seroprevalence of 2.3% and immunoglobulin M (IgM) of 0.6% 14 . Another study between March and July 2021 reported an IgG/IgM antibodies seroprevalence of 89% among the unvaccinated health facility staff 15 . As of the time of writing, there are no reports on the seroprevalence of SARS‐CoV‐2 IgG/IgM antibodies in PLWH in Sierra Leone.…”
Section: Introductionmentioning
confidence: 99%